2020
DOI: 10.1177/0003489420952481
|View full text |Cite
|
Sign up to set email alerts
|

General Complications after Endoscopic Sinus Surgery in Smokers: A 2005-2016 NSQIP Analysis

Abstract: Background: Exposure to cigarette smoke has been associated with a higher incidence of postoperative complications across a variety of surgical specialties. However, it is unclear if smoking increases this risk after endoscopic sinus surgery (ESS). Because complication rates after ESS are relatively low, a large national database allows for a statistically meaningful study of this topic. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) dataset from 2005 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
6
1
1
Order By: Relevance
“…Previous studies have also reported an increased risk of infection in Black compared with White patients in orthopedic surgery (26,27). We further corroborate a similar finding in tympanoplasty surgery noting that American Indian/Alaska Native patients were more likely to suffer from postoperative superficial SSIs (OR, 5.503) and Black patients of deep SSIs (OR, 6.292), even after adjusting for smoking, which has been linked to increased rates of infection (27–30). We again acknowledge that, although the overall ORs show a large disparity, the overall rate of these complications in this analysis was low, with 0.6 and 0.2% of patients experiencing superficial and deep SSIs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have also reported an increased risk of infection in Black compared with White patients in orthopedic surgery (26,27). We further corroborate a similar finding in tympanoplasty surgery noting that American Indian/Alaska Native patients were more likely to suffer from postoperative superficial SSIs (OR, 5.503) and Black patients of deep SSIs (OR, 6.292), even after adjusting for smoking, which has been linked to increased rates of infection (27–30). We again acknowledge that, although the overall ORs show a large disparity, the overall rate of these complications in this analysis was low, with 0.6 and 0.2% of patients experiencing superficial and deep SSIs, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…16 Smoking, which can cause similar microvascular compromise, was also recently found to predispose ESS patients to surgical site infections. 19 However, despite what these studies may suggest a priori, we find no evidence of increased infectious burden for the diabetic patient. Given that reinfection after surgery has been shown to be a significant predictor of readmission risk, 7 these results are doubly reassuring.…”
Section: Discussioncontrasting
confidence: 73%
“…14,15 Numerous otolaryngologic studies have utilized the NSQIP to conduct retrospective analyses regarding surgical procedures. [16][17][18] This analysis includes only de-identified patient information that was deemed exempt from the Rutgers New Jersey Medical School Institutional Review Board, Newark, NJ, in accordance with their policy.…”
Section: Databasementioning
confidence: 99%